NGHIÊN CỨU KHẢ NĂNG HẤP PHỤ ASEN TRÊN VẬT LIỆU NANO α-Fe2O3 - Đại, Lưu Minh; Tố Loan, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
The nanosized α-Fe2O3 and nanosized α-Fe2O3 coated sand were synthesised for arsenic adsorption. The sorption treatment of both As (III) and As (V) in water solution was investigated. The results showed that As (V) was adsorbed better than As (III) in the same conditions. The nanosized a-Fe2O3 yielded maximum sorption capacity of 30.86 mg/g for As (III) and 35.09 mg/g for As (V) and the nanosized α-Fe2O3 coated sand yielded maximum sorption capacity of 1.18 mg/g for As (III) and 1.30 mg/g for As (V) according to the Langmuir isotherm.